2014
DOI: 10.3329/sja.v11i2.18409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Azotobacter on Growth and Yield of Maize

Abstract: A field experiment was conducted to study the effect of Azotobacter on growth and yield of maize (variety Rampur composite) . Analysis of variance showed that grain yield, plant height, ear height, ear length, kernel per rows and 1000 grain weight were significantly affected with treatments. Only inoculation of Azotobacter increased 15 to 35% grain yield over non inoculated treatments. The benefit of Azotobacter inoculation was higher in the absence of chemical fertilizer application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 3 publications
3
9
0
3
Order By: Relevance
“…Pupuk organik dalam bentuk Azotobacter meningkatkan hasil dengan efek positif terhadap tinggi, bobot dan indeks daun serta hasil tanaman jagung (Peng et al, 2013). Pada percobaan lapangan, inokulasi Azotobacter tanpa penambahan pupuk anorganik meningkatkan hasil jagung antara 15-30% dibandingkan dengan tanaman yang tidak diinokulasi (Baral and Adhikari, 2013).…”
Section: Penggunaanunclassified
“…Pupuk organik dalam bentuk Azotobacter meningkatkan hasil dengan efek positif terhadap tinggi, bobot dan indeks daun serta hasil tanaman jagung (Peng et al, 2013). Pada percobaan lapangan, inokulasi Azotobacter tanpa penambahan pupuk anorganik meningkatkan hasil jagung antara 15-30% dibandingkan dengan tanaman yang tidak diinokulasi (Baral and Adhikari, 2013).…”
Section: Penggunaanunclassified
“…Similarly, results were obtained in second season except plant height and total carbohydrate obtained by Single hybrid 30 K 8(SH30k8) and F2 (100 % mineral fertilizer).This is true in both seasons. Several investigators pointed out that yield and its components were increased by using (SH30k8) and F6(PYH-3084) (Elamin, and Elagib 2001;Kuepper 2003;Efthimiadouet al, 2010;Baral and Adhikari 2013;Ghasemiet al, 2013;Beyranvet al, 2013 andKhaksaraet al, 2014).…”
Section: -The Interaction Between Corn Hybrids and Biomineral Fertilimentioning
confidence: 99%
“…Moreover Azotobacter increased number of kernels per row from 40.2 to 43.2 (Table 7 and 8) INM including vermicompost showed best results in yield parameters of maize like number of grains per cob, weight of the cob, 100 seed weight and yield (Kannan et al, 2013). Beigzade et al (2013) showed that phospho- Baral and Adhikari (2013) reported that the numbers of kernels per row was signifi cantly infl uenced by Azotobacter…”
Section: Number Of Kernels Per Rowmentioning
confidence: 99%
“…In both irrigation treatments with increasing of chemical and bio fertilizer plant height was increased (Table 11 and 12). Baral and Adhikari (2013) reported Azotobacter increased plant height in maize. Alnoaim and Hamad (2004), reported that by using of bio-fertilizers with using of N fertilizer the highest plant height, number of tiller and grain yield of rice (Oryza sativa) were achieved.…”
Section: Plant Heightmentioning
confidence: 99%